The archaic Acheulean lithic industry of the Cretone basin (Latium, central Italy). (September 2015) - Ceruleo, P.; Marra, F.; Pandolfi, L.; Petronio, C.; Salari, L.
Abstract: A rich record of Lower Paleolithic lithic industries collected within the lacustrine basin of Cretone (Latium, Central Italy) is described in detail, showing the occurrence of two distinct tool assemblages. According to the geochronolgy data constraining the evolution of the lacustrine basin, in which the largest portion of the sedimentary filling correlates with the depositional cycles linked to Marine Isotopic Stages (MIS) 15 and 13, most of the Cretone lithic industry shows the characters of an archaic Acheulean facies, relatively rich in bifacials with lithic industry on flake and roughly cut pebbles (often tending to two-sided chopper), that has similarities with the oldest Italian complexes (e.g.: Isernia - La Pineta). In contrast, a smaller record of artifacts displaying features kin to the early Middle Paleolithic complexes of this region, is likely associated with later frequentation of the area during MIS 9 through 7, when lacustrine conditions were largely superseded by a fluvial-palustrine environment, to which limited sedimentary deposits are associated, and migrated to the eastern margin of the basin, where a smaller lake persisted until MIS 5. The recognition of the described "archaic" facies of Acheulian industry within a geochronologically constrained context provides new data on the lower - middle Paleolithic transition in central Italy and allows us to present a comparative review of other important sites of this region. Highlights: We describe a rich record of Lower Paleolithic lithic industries collected within the lacustrine basin of Cretone (Latium, Central Italy) We show the occurrence of two distinct tool assemblages. An archaic Acheulean assemblage occur within lacustrine deposits correlated with MIS 15. A later early Middle Paleolithic assemblage is associated with later frequentation of the area during MIS 9 through 7 We provide new data on the lower - middle Paleolithic transition in central Italy and present a comparative review of other important sites of this region.